Impacting Digital Transformation of Human Resource Management on Enterprise Competitive Capacity: A Case Study in Vietnam - Lu Phi Nga; Phan Thanh Tam (Qubahan Academic Journal)
In the era of rapidly developing digital technology, digital transformation has become an inevitable trend globally, and Vietnam is also following that trend. The digital transformation of human resource management is necessary for optimizing human resources, improving labor productivity, and enhancing competitiveness. This study analyzes the key factors affecting the competitive capacity of small and medium enterprises (SMEs) in Vietnam and provides recommendations to improve this process. The research utilizes a mixed-methods approach, combining qualitative interviews with 30 business managers and a quantitative survey of 650 managers across five provinces and one city. Using structural equation modeling (SEM), the study identifies five critical factors influencing competitive capacity: human resource management, corporate culture, online public relations, digital transformation, and creative innovation. Among these, digital transformation has the strongest impact on enterprise competitiveness (β = 0.341, p < 0.001), followed by corporate culture (β = 0.203, p < 0.001) and creative innovation (β = 0.165, p < 0.001). The findings highlight the necessity of integrating digital tools into human resource management (HRM), fostering a supportive corporate culture, and leveraging innovation to enhance business performance. These insights offer significant contributions to both academic research and practical management strategies. The study proposes key policy recommendations, including targeted digital upskilling, investment in technological infrastructure, and corporate culture reforms to facilitate digital transformation in Vietnamese SMEs.